Efficacy and safety of multiple doses of levomilnacipran extended-release for the treatment of major depressive disorder - Huang Q; Zhong X; Yun Y; Yu B; Huang Y (Neuropsychiatric Disease and Treatment)
Qunlian Huang,1 Xiaoyan Zhong,1 Ye Yun,1 Bin Yu,2 Yilan Huang1 1Department of Pharmacy, The Affiliated Hospital of Southwest Medical University, 2Department of Clinical Pharmacy, School of Pharmacy, Southwest Medical University, Luzhou, Sichuan Province, People’s Republic of China Objective: The aim of this meta-analysis was to evaluate the efficacy and safety of levomilnacipran extended-release (ER) in the treatment of major depressive disorder (MDD). Methods: Randomized controlled trials were searched by electronic databases. Unpublished data were also searched by the relevant websites. Weighted mean difference (WMD) and risk ratio (RR) with 95% confidence interval (CI) were calculated and pooled using fixed-effects model or random-effects model. Results: Five randomized placebo-controlled trials including 2,637 patients were analyzed. Compared with placebo, levomilnacipran ER had a greater reduction in the Montgomery–Åsberg Depression Rating Scale (MADRS) total score and Sheehan Disability Scale (SDS) total score (MADRS: WMD -3.49 [95% CI -4.28, -2.70; P<0.00001]; SDS: WMD -2.41 [95% CI -3.05, -1.77; P<0.00001]). Significantly more patients in levomilnacipran ER achieved MADRS response rate (RR 1.35 [95% CI 1.23, 1.47; P<0.00001]) and MADRS remission rate (RR 1.30 [95% CI 1.06, 1.59; P=0.01]). In terms of safety, more patients discontinued due to adverse events (AEs) in levomilnacipran ER compared with placebo (RR 3.15 [95% CI 2.26, 4.39; P<0.00001]), but it was generally well tolerated in each eligible trial. The most common AEs were nausea, delay in ejaculation, erectile dysfunction, tachycardia, headache and increase in heart rate. Conclusion: Levomilnacipran ER is a safe and effective short-term treatment for MDD (≤10 weeks). Long-term and head-to-head trials comparing levomilnacipran ER with other antidepressants are needed to confirm the conclusion. Keywords: levomilnacipran ER, SNRI, major depressive disorder, meta-analysis